A theoretical analysis on the effect of containers on the microwave heating of materials. (March 2017) - Bhattacharya, Madhuchhanda; Punathil, Lineesh; Basak, Tanmay
Abstract: Microwave heating is generally performed by positioning the sample within a container. The container can reflect, absorb or transmit microwaves based on the dielectric properties and that can influence the microwave heating characteristics of the sample. This work is an attempt to theoretically analyze the alteration of the microwave heating characteristics of materials due to the use of either a low-lossy alumina container or a high lossy SiC container. The heating characteristics have been simulated for the high-lossy beef and low-lossy bread samples of a fixed dimension by solving the coupled energy balance equation and detailed Helmholtz wave propagation equations within the sample-container assembly. It has been shown that the microwave heating characteristics can be significantly altered in the presence of the container based on the relative dielectric properties of the materials. The alumina container has been found to be efficient to enhance the microwave heating efficiency of the high lossy material such as beef, while the rapid microwave heating of the SiC container has been found to be beneficial to enhance the heating of the low lossy material such as bread in some cases.